Exploring Organizational Culture: Teaching Notes on Metaphor, Totem, and Archetypal Images - Starr-Glass, David (Journal of management education, 2004)
The author introduces an experiential appreciation of organizational culture into a strategic management course. Students were asked to retrieve and to reflect on metaphors, totemic systems, and archetypal imagery associated with their college. Each technique was selected to explore the oblique views of organizational process and dynamics that students possessed. Initially, this encounter was designed to sensitize students to alternative strategic considerations. Although this may have been partially realized, it seems that the experience was more significant in allowing students to realize that they had unconscious impressions of an organizational culture and that these sentiments contributed to their interaction with the college.